Reprogramming Macrophage Metabolism and its Effect on NLRP3 Inflammasome Activation in Sepsis - Luo, Ruiheng; Li, Xizhe; Wang, Dan (Frontiers in Molecular Biosciences, 2022)
Sepsis, the most common life-threatening multi-organ dysfunction syndrome secondary to infection, lacks specific therapeutic strategy due to the limited understanding of underlying mechanisms. It is currently believed that inflammasomes play critical roles in the development of sepsis, among which NLRP3 inflammasome is involved to most extent. Recent studies have revealed that dramatic reprogramming of macrophage metabolism is commonly occurred in sepsis, and this dysregulation is closely related with the activation of NLRP3 inflammasome. In view of the fact that increasing evidence demonstrates the mechanism of metabolism reprogramming regulating NLRP3 activation in macrophages, the key enzymes and metabolites participated in this regulation should be clearer for better interpreting the relationship of NLRP3 inflammasome and sepsis. In this review, we thus summarized the detail mechanism of the metabolic reprogramming process and its important role in the NLRP3 inflammasome activation of macrophages in sepsis. This mechanism summarization will reveal the applicational potential of metabolic regulatory molecules in the treatment of sepsis.